Corporate Sustainability Orientation, Enforcement of Regulatory Policy and Strategic Leadership for Sustainability Practices Among Food Manufacturing Companies in Sarawak - Peter, Jambai (Unimas, 2025)
food manufacturing industry in Sarawak faces sustainability challenges due to inconsistencies in Corporate Sustainability Orientation (CSO) and varying levels of Enforcement of Regulatory Policy (ERP). While Sustainability Practices (SP) are essential for long-term resilience, adoption remains uneven. This study examines the direct impact of CSO on SP, the mediating role of ERP, and the moderating effect of Strategic Leadership (SL). A quantitative survey of 69 food manufacturing firms was analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). Findings confirm that CSO significantly influences SP, with ERP as a strong mediator. However, SL does not significantly moderate the CSO-ERP relationship, indicating regulatory enforcement plays a stronger role than leadership influence. These results align with Institutional Theory, emphasizing coercive regulatory pressures in driving sustainability practices. This study highlights the need for stronger regulatory oversight, digital compliance monitoring, and targeted incentives for SMEs. While SL does not moderate regulatory enforcement, corporate leaders should integrate sustainability into governance and performance metrics. Aligning sustainability initiatives with Sarawak’s Post COVID-19 Development Strategy 2030 (PCDS 2030) is crucial for long-term sustainability. Future research should explore broader industry contexts to strengthen sustainability governance. Keywords: Corporate Sustainability Orientation, Sustainability Practices, Regulatory Compliance, Strategic Leadership, Food Industry and SMEs. Keywords: Corporate Sustainability Orientation, Sustainability Practices, Regulatory Compliance, Strategic Leadership, Food Industry